Design and Implementation of a Mobile-Based Language Learning Information System - Imam Mualim; Nuari Anisa Sivi; Ruri Supatmi; Roro Fatikhin; Najla Asyila; Arjun Firmansyah (PT. GWEX NET PUBLISHER, 2026)
The rapid development of information and communication technology has driven transformation in various areas of life, including education. One continuously evolving innovation is the use of mobile devices as learning media that are flexible, interactive, and easy for users to access anytime and anywhere. This research aims to design and implement a mobile-based language learning information system that can improve the effectiveness and efficiency of the users’ learning process. The research method used includes stages of analyzing user needs, system design, application implementation, and system testing to ensure the application can operate according to the expected objectives. The developed system is equipped with various key features, such as learning materials for reading, writing, speaking, and listening, interactive exercises, learning evaluation, as well as discussion and user feedback features to enhance interaction between users and the learning system. In addition, the application is designed with a simple and user-friendly interface so it can help users understand the material in a more structured and engaging way. The research results show that the system built is able to provide easy access to learning, increase user engagement in the learning process, and help improve understanding of language learning materials more effectively. System testing also shows that the application can run well on various mobile devices and provides a more efficient learning experience. Thus, this mobile-based language learning information system is expected to be an alternative solution to support modern learning processes and improve the quality of language learning in the digital era.